Theoretical foundations and practices of reengineering realization in construction - S. B. Sborshchikov; N. V. Lazareva (Vestnik MGSU)
Introduction. The issues related to the life cycle of technical solutions, the peculiarities of their manifestation and the specifics of management in construction are considered. The analysis allowed to formulate regularities in the chosen subject area, as well as recommendations for improving the efficiency of the corporate regulatory system of investment and construction activities through reengineering. To confirm their judgments, the authors cite practical experience in identifying and regulating technical solutions used in the design, construction and operation of nuclear power plants (NPP).Materials and methods. The theoretical foundations of the analysis of reengineering in construction were the provisions of the following concepts: life cycle management; logistics of regulatory influences; technical rationing; sustainable development, as well as methods of system analysis such as: logical-semantic and simulation modelling, retrospective and functional-structural methods, the reserve of domestic and foreign scientists in the context of the research.Results. The classification of technical solutions in construction is proposed, the regularities of development of the life cycle of technical solutions for capital construction facilities are determined, as confirmation of the above provisions, an analysis of the practice of identification and regulation of technical solutions used in the design, construction and operation of nuclear power plants (NPP) is given.Conclusions. The life cycle of technical solutions in construction is characterized by the manifestation of both general and specific patterns, their consideration when creating a management system of the same name should contribute to the effective transfer of innovations to the production sector, the formation of competitive advantages for construction organizations by improving the quality of construction products, and for operating organizations lengthening the life cycle of capital construction facilities and reducing the cost of operating costs.